Obesity as Risk Factor of Gastroesophageal Reflux Disease - Naomi, Diah Anis (Majority, 2014)
Abstract Reflux disease is one of the dominant clinical problems in the field of Gastroenterology. Over the past 40 years, the incidence of reflux disease increased. Pathological state which gastroesophageal reflux causes symptoms and complications is called Gastroesophageal Reflux Disease (GERD). GERD is influenced by various factors, genetic factors and environmental factors. Obesity is becoming a part of the environmental factors that play a role in the occurrence of GERD, through the mechanism of the increase in intra-abdominal pressure and through active metabolism of visceral fat. This summary is aimed to explore the potential mechanisms responsible for the association between GERD and obesity, and to better understand the possible role of weight loss as a therapeutic approach for GERD. Keywords: GERD, obesity, reflux. Abstrak Penyakit refluks adalah salah satu masalah klinis yang dominan dalam bidang Gastroenterologi. Selama 40 tahun terakhir, kejadian penyakit refluk meningkat. Keadaan patologis dimana refluks gastroesofageal menyebabkan gejala dan komplikasi disebut penyakit refluks gastroesofageal (Gastroesophageal Reflux Disease/GERD). GERD dipengaruhi oleh berbagai faktor yaitu faktor genetik dan faktor lingkungan. Obesitas menjadi bagian dari faktor lingkungan yang berperan dalam terjadinya GERD. Obesitas menjadi risiko GERD melalui mekanisme peningkatan tekanan intra-abdomen dan melalui hasil metabolisme aktif lemak viseral. Artikel review ini bertujuan untuk mengeksplorasi mekanisme obesitas sebagai faktor risiko GERD sehingga menurunkan berat badan dapat menjadi salah satu penatalaksanaan pada GERD. Kata kunci: GERD, obesitas, refluks.